Genetic NMDA receptor deficiency disrupts acute and chronic effects of cocaine but not amphetamine - Ramsey, Amy J. (Neuropsychopharmacology, 2008)
NMDA receptor-mediated glutamate transmission is required for several forms of neuronal plasticity. Its role in the neuronal responses to addictive drugs is an ongoing subject of investigation. We report here that the acute locomotor-stimulating effect of cocaine is absent in NMDA-receptor deficient mice (NR1-KD). In contrast, their acute responses to amphetamine and to direct dopamine receptor agonists are not significantly altered. The striking attenuation of cocaine's acute effects is not likely explained by alterations in the dopaminergic system of NR1-KD mice, since most parameters of pre-and post-synaptic dopamine function are unchanged. Consistent with the behavioral findings, cocaine induces less c-Fos expression in the striatum of these mice, while amphetamine-induced c-Fos expression is intact. NR1-KD mice can become sensitized and display conditioned place preference to cocaine; however, these behaviors are attenuated and develop more slowly in mutant animals. Our results highlight the importance of NMDA receptor-mediated glutamatergic transmission specifically in cocaine actions, and support a hypothesis that cocaine and amphetamine elicit their effects through differential actions on signaling pathways.